Foreignization and Domestication as Strategies in Translation and the Translation of Chinua Achebe’s into French - Anyabuike, Cyril (EBSU Journal of Social Sciences and Humanities, 2021)
The translator as a professional is at liberty to choose any strategy of translation while exercising his function. The goal that propelled him into action as well as the possible effects of the work on his target audience are some of the factors that could inform his choice of strategy. Consequently, he may adopt domestication or foreignization as a strategy while translating. In this work, we examined the two concepts – foreignization and domestication with a view to placing them in their proper perspectives. We also examined the strategy adopted by Michel Ligny while translating into French. We concluded, after due analysis, that the translator opted for foreignization. We suggested that a glossary and footnotes should be added to make the French version of the text more accessible to the Francophone reading public.